2016
DOI: 10.1111/aogs.13041
|View full text |Cite
|
Sign up to set email alerts
|

Performance of mRNA‐ and DNA‐based high‐risk human papillomavirus assays in detection of high‐grade cervical lesions

Abstract: The mRNA-based Aptima assay and the extensively studied DNA-based HC2 test performed equally well in detecting high-grade cervical lesions. Our data contribute to the growing evidence base indicating that the mRNA-based Aptima assay could be used for the triage of patients with HPV-associated cervical disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 32 publications
(51 reference statements)
4
11
0
Order By: Relevance
“…The current study assessed the follow‐ups of both the Cervista and Aptima tests in women with LSIL cytology and the results demonstrated that both platforms had similar clinical performance in detecting CIN2 + lesions. In the current study, we failed to reproduce the improved specificity in the general population with the Aptima assay, a result that is consistent with recent reports comparing the clinical performance of Aptima and HC2, which also demonstrated similar performance, including specificity …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The current study assessed the follow‐ups of both the Cervista and Aptima tests in women with LSIL cytology and the results demonstrated that both platforms had similar clinical performance in detecting CIN2 + lesions. In the current study, we failed to reproduce the improved specificity in the general population with the Aptima assay, a result that is consistent with recent reports comparing the clinical performance of Aptima and HC2, which also demonstrated similar performance, including specificity …”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have demonstrated that the Aptima HrHPV assay has similar sensitivities but superior specificities for precancerous lesions (CIN2/3) when compared with the HPV DNA testing platforms (mostly the HC2 method), and suggested the HPV messenger RNA (mRNA) test is a better triage test for women with LSIL. However, other evidence demonstrated that there was no significant difference between HPV DNA‐based and RNA‐based assays with regard to clinical performance for the detection of high‐grade cervical lesions . In the current study, we assessed the histopathologic follow‐up of the Aptima HPV RNA and Cervista HPV DNA assays in women with LSIL cytology in a large academic institution to evaluate which was the better strategy for the triage of women with LSIL cytology.…”
Section: Introductionmentioning
confidence: 95%
“…Recent studies suggest that HPV mRNA testing has improved specificity for grade 2 cervical intraepithelial neoplasia (CIN2) or worse (≥CIN2) compared with HPV DNA assays . However, other studies concluded that there was no significant difference between HPV DNA and RNA testing methods in clinical performance for the detection of high‐grade cervical lesions . The purpose of the current study was to analyze the performance of the 2 most common HPV testing platforms (Cobas and Aptima) in detecting high‐grade cervical lesions that were confirmed by biopsy.…”
Section: Introductionsupporting
confidence: 91%
“…[12][13][14] However, other studies concluded that there was no significant difference between HPV DNA and RNA testing methods in clinical performance for the detection of high-grade cervical lesions. 15,16 The purpose of the current study was to analyze the performance of the 2 most common HPV testing platforms (Cobas and Aptima) in detecting high-grade cervical lesions that were confirmed by biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies and a meta‐analysis report higher specificity of the Aptima HPV assay and comparable sensitivity to the HPV DNA detection assay HC2 for the detection of CIN2+ in both colposcopy referral and primary screening settings …”
Section: Introductionmentioning
confidence: 99%